Truth of the court sentence - Bibilo, Valentina N. (Journal of the Belarusian State University. Law, 2020)
The purpose of proof in criminal proceedings is to establish the truth. It is necessary to distinguish between two types of truth: substantive and formal. The substantive (objective-subjective) truth is established through proof. The formal truth lies in the use of predefined conditions, rules, technical standards, presumptions, prejudices. The combination of substantive and formal truth constitutes the legal truth. The truth of the court sentence is determined by the presence of legal truth.
Keywords: criminal proceeding; court; cognition; proof; sentence; truth; argumentation